Value of Surgical and Nonsurgical Treatment for Sleep Apnea: A Closer Look at Health Care Utilization. (16th February 2023) - Abdelwahab, Mohamed; Marques, Sandro; Huang, Allen; De Moraes, Thyago P.; Previdelli, Isolde; Cruz, June Alisson Westarb; Al‐Sayed, Ahmed A.; Capasso, Robson
Abstract: Objective: To determine how surgery, continuous positive airway pressure (CPAP), and no treatment impact health care utilization in patients who have obstructive sleep apnea (OSA). Study Design: This is a retrospective cohort study of patients between the ages of 18 and 65 that were diagnosed with OSA (9th International Classification of Diseases) from January 2007 to December 2015. Data were collected over 2 years, and prediction models were generated to evaluate trends over time. Setting: A population‐based study using real‐world data and insurance databases. Methods: A total of 4, 978, 649 participants were identified, all with at least 25 months of continuous enrollment. Patients with previous soft tissue procedures not approved for OSA (nasal surgery), or without continuous insurance coverage were excluded. A total of 18, 050 patients underwent surgery, 1, 054, 578 were untreated, and 799, 370 received CPAP. IBM Marketscan Research database was utilized to describe patient‐specific clinical utilization, and expenditures, across outpatient, and inpatient services, and medication prescriptions. Results: When the cost of the intervention was eliminated in the 2‐year follow‐up, the monthly payments of group 1 (surgery) were significantly less than group 3 (CPAP) in overall, inpatient, outpatient, and pharmaceutical payments ( p  < .001). The surgery group was associated with less cumulative payments compared to the other 2 groups when the cost of the intervention (CPAP or surgery) was eliminated in all comorbidities and age groups. Conclusion: Treating OSA with surgery can lessen overall health care utilization compared to no treatment and CPAP.